PENGARUH PEMBERIAN PANGAN SETENGAH JADI BERBASIS IKAN (SOSIS ANALOG) DENGAN KECUKUPAN PROTEIN BALITA DALAM UPAYA PENURUNAN STUNTING DI KABUPATEN SELUMA - Eliana Eliana; Emy Yuniantini; Kamsiah Kamsiah; Andi Eka Yunianto (GIZI INDONESIA, 2022)
The Stunting rate in Seluma Regency is quite high in Bengkulu Province reaching 38.5 percent. The decline in the Stunting rate in Seluma in 2019 was 10.35 percent or down 28.15 percent from 38.5 percent. The purpose of this study was to analyze the effect of providing fish-based semi-finished food (analog sausage) as an alternative to increasing protein adequacy to reduce stunting rates in Seluma Regency. The study used a quasi-experimental design by presenting analog sausages to children under five, which was held from July to November 2021. The research location is in Seluma Regency. The population is children under five in Seluma Regency with a total sample of 75 children under five determined by purposive sampling. The intervention was carried out by giving 50 g/day sausages in intervention group I and 100 g/day in intervention group II, while the control group was given 50 g/day commercial sausages with an intervention duration of 4 weeks. Data analysis using the Anova test to analyze differences in energy and protein consumption and status of the intervention and control groups. The results showed significant differences in energy adequacy levels (TKE) and protein adequacy levels (TKP) in the three groups before and after the analog sausage intervention. The results of the Anova test showed that there was no significant difference in nutritional status in the three groups (p0.05)